Cyber Security Awareness dalam Penggunaan Geo- Tagging di Media Baru dan Potensi Implikasinya Terhadap Keamanan Nasional - Adji Yuwana Pratama; Ridwan (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2024)
This article on cyber security awareness in the use of geo-location in New media and its potential implications for national security explains the phenomenon of digital activities that are considered to endanger national security. The activities in question include geo-location tagging, video and photo recording in vital state objects, especially the TNI headquarters. This research uses a qualitative method with a descriptive approach with literature study data retrieval techniques In this research the author uses a cyberpolitics perspective The results of the analysis in this study are the lack of understanding of cyber threats and attacks from state apparatus and civilians. Therefore, the author suggests that the government make regulations governing how to move in vital objects owned by the state, especially the TNI and Polri, the need for socialization to the apparatus and civilians regarding the importance of Cyber Security Awareness and cyber security systems that are relevant to the latest potential threats